Association Between Pre-diagnostic Dietary Supplements Intake and Ovarian Cancer Survival: Findings From a Prospective Cohort Study in Chinese Women - Gu, Jia-Hui; Gong, Ting-Ting; Wu, Qi-Jun; Liu, Fang-Hua; Wen, Zhao-Yan; Gao, Chang; Wei, Yi-Fan; Yang, Zhuo (Frontiers in Nutrition, 2021)
Background: As a result of a limited number of studies and inconsistent findings, there remains uncertainty in whether pre-diagnostic dietary supplements intake affects survival after ovarian cancer (OC) diagnosis. Methods: The association between pre-diagnostic dietary supplements intake and all-cause OC mortality was examined in the OC follow-up study, which included a hospital-based cohort (n = 703) of Chinese women diagnosed with OC between 2015 and 2020. Pre-diagnostic dietary supplements information was collected using self-administered questionnaires. Deaths were ascertained up to March 31, 2021, via death registry linkage. Cox proportional hazards were used to estimate hazard ratios (HR) and 95% confidence intervals (CI) for the aforementioned association. Results: A total of 130 women died during the median follow-up of 37.2 months (interquartile: 24.7–50.2 months). We found no evidence that any pre-diagnostic dietary supplements intake compared with never is associated with OC survival (HR = 0.75, 95%CI: 0.47–1.18). Furthermore, our study suggested no association for ever supplements intakes of vitamin A (HR = 0.48, 95%CI: 0.07–3.46), vitamin C (HR = 0.64, 95%CI: 0.27–1.54), vitamin D (HR = 1.19, 95%CI: 0.28–5.03), vitamin E (HR = 0.47, 95%CI: 0.06–3.87), multivitamin (HR = 0.49, 95%CI: 0.14–1.67), calcium (HR = 0.96, 95%CI: 0.53–1.72), and fish oil/DHA (HR = 0.31, 95%CI: 0.04–2.37) with OC survival. Interestingly, we only found a detrimental effect of vitamin B supplementation intake (HR = 3.78, 95%CI: 1.33–0.69) on OC survival. Conclusions: We found no evidence that any pre-diagnostic dietary supplements intake is associated with OC survival. Considering lower exposure of dietary supplements before OC diagnosis in the present study, further studies are warranted to confirm these findings.